The Effect of The CTL Model Assisted by Digital Pop-Up Books on The Learning Outcomes of IPAS Subject In Fourth Grade Elementary School - Damayanti, Defia; Rukmana, Diki (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
The low learning outcomes of IPAS elementary school students, especially in the material on changes in the form of abstract objects, shows the need for a more contextual and visual learning approach. So far, various studies have discussed the CTL model and digital pop-up book media separately, but there are still limited studies that combine these models and learning media.therefore, This study aims to examine the effect of applying the Contextual Teaching and Learning (CTL) model, supported by digital pop-up book media, on the learning outcomes of Grade IV elementary school students in the subject of Integrated Natural and Social Sciences (IPAS), specifically on the topic of changes in the states of matter. The research employed a quantitative approach with a pre-experimental one-group pretest–posttest design, involving 30 students as participants. The findings indicated that the data were normally distributed. Furthermore, the results of the paired sample t-test revealed a significant difference between the pretest and posttest scores (tcount 7.758 > t table 2.042 and sig. 0.000) The calculation of the effect size using Cohen’s d yielded a value of 1.416, which falls within the very large category. Accordingly, it can be concluded that the implementation of the Contextual Teaching and Learning (CTL) model, supported by digital pop-up book media, is effective in enhancing the learning outcomes of Grade IV elementary school students in science subjects, particularly on the topic of changes in the states of matter.